DESIGN OF HIGHLY REDUNDANT FAULT TOLERANT CONTROL FOR AIRCRAFT ELEVATOR SYSTEM - Tayyeb, Muhammad; Riaz, Umar; Amin, Arslan Ahmed; Saleem, Omer; Arslan, Muhammad; Shahbaz, Muhammad Hamza (Journal of Applied Engineering Science, 2020)
Elevators are surfaces of flight control, typically at the rear of an aircraft to control the pitch of the plane, the angle of attack and the wing lift. The most critical actuation device is longitudinal aircraft control, and its failures will result in a catastrophic aircraft crash. This paper proposes a Highly Redundant Fault Tolerant Control (HRFTC) policy for the aircraft to accommodate faults in the critical sensors and actuators. Modified Triple Modular Redundancy (MTMR) has been proposed for the sensors and Dual Redundancy (DR) has been proposed for the actuators. The working of control laws, pilot order, signal conditioning, and failure are elaborated. Furthermore, the PID controller is used for the adjustment of the position of the elevator by comparing it with a set point. The results show that when a fault occurs, the system detects it successfully and tolerates it quickly without disturbing the flight of aircraft. The study is significant for the avionics industry for manufacturing highly reliable machines for human and environmental safety.